Money Does Not Grow on Trees: An Argument for Usury - Labat, Alyssa; Block, Walter 1941- (2012)
Usury, charging a higher interest rate than thought by some to be “fair,” has had and still has, a bad press. Historically, it was heavily punished. It was then, and all too often is now, thought to be exploitative. Yet, as even the most economically unsophisticated must realize, both sides of these transactions must necessarily gain at least in the ex ante sense, otherwise one or the other would refuse to enter into the deal in the first place. The present paper is an attempt to justify the practice of charging interest on loans, at any rate agreeable to both borrowers and lenders.
Keywords: E51; E4; Lending; Borrowing; Economic Freedom; Free Enterprise; Usury